Analisis Karakteristik dan Sumber Pendapatan Petani (Studi Kasus Petani Sayur di Desa Morome Kecamatan Konda Kabupaten Konawe Selatan) - Agus Eko Priono; Yani Taufik; Rosmawaty Rosmawaty (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
This study aims to: (1) determine the characteristics of farmers; (2) Knowing how much income is obtained from vegetable farming and (3) Knowing the relationship between farmer characteristics and farmers' income. This research was conducted from January to March 2021. The sampling technique used was the census method, and the data analysis used was descriptive, income analysis, and Spearman Rank Correlation. The results of this study indicate that the level of education of farmers is dominated by farmers who are junior high school graduates (SMP), the largest vegetable farming experience is more than 10 years, the highest land area is 0.5-2 Ha and family dependents of vegetable farmers are included in the family category. small with dependents above 2-3 people. Based on the Spearman Rank Correlation analysis, the relationship between farmer characteristics and income of land area shows a significant category, meaning that there is a relationship between land area and income of vegetable farmers. Meanwhile, for the category of education level, experience and family responsibilities are included in the insignificant or unrelated category.